Creepy pair of underwear! - Reynolds, Aaron, 1970-; Brown, Peter, 1979- (New York : Simon & Schuster Books for Young Readers, 2017)
"A young rabbit is frightened by his underwear"--
Keywords: Rabbits -- Fiction; Underwear -- Fiction; Fear -- Fiction